Anterior tarsal tunnel syndrome - (:unkn) unknown (My University, 2000)
Three hundred twenty patients complaining of pain and/or numbness of their feet were evaluated in our Clinical Neurophysiology Laboratory. Nerve conduction studies of deep peroneal, superficial peroneal, sural and posterior tibial nerves were studied bilaterally. Needle electromyography (EMG) of anterior tibial, long peroneal, abductor hallucis longus, extensor hallucis longus, gastrocnemius and extensor digitorum brevis muscles were examined bilaterally. Nerve conduction studies of 25 healthy volunteer subjects (16 female, 9 male, age range 36-70, mean age 52.82 +/- 8.8) with no complaint composed the control group. Fourteen of these patients (8 female, 6 male, age range 40-70, mean age 55.73 +/- 12.04) were found to have anterior tarsal tunnel syndrome (anterior TTS) bilaterally or unilaterally. In the patients with anterior TTS, the nerve conduction studies revealed deep peroneal nerve distal latency as 6.5 +/- 1.9 msec; the amplitude as 1.8 +/- 1.3 mV at the ankle level; and the conduction velocity as 41.5 +/- 5.9 m/sec in the distal segment. When these values were compared with the control group statistically, results were found highly significant (p < 0.005). Needle EMG findings in the anterior TTS group showed only in the extensor digitorum brevis muscle. Other nerves and muscles were normal. All patients with anterior TTS were performing Namaz for years, and none of them had the predisposing factor which may cause entrapment neuropathy. So, we suggest that chronic prolonged stretching of the deep peroneal nerve on the dorsum of the foot during Namaz may cause anterior TTS.
Keywords: Adult; Female; Humans; Middle Aged; Aged; Male; Islam; Muscle, Skeletal; Reaction Time; Neural Conduction; Tibial Nerve; Electromyography; Religion and Medicine; Sural Nerve; Peroneal Nerve; Forefoot, Human; Tarsal Tunnel Syndrome